(3GdefgL GdefjQ aj eYQaI CSeGA GdYbGbjQs ((3eOjf YHO GdQMef s)
(3ChdgG (B:s
(3aEfi deG QCjJ CSeGA GdYbGbjQ GdWHjI bO OQS QSegG , hJYPQ Ydi GdWdGH s
(3BNQgG (B:s
(3GdbhdfL GdLjdi JeGe gh GdBSaGY hgh QZhI GdHMQ s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B593 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B190 s
Keywords: (3GdWHs